PROMOTING DIALOGUE SPEECH FOR PRE-SCHOOL CHILDREN IN PROBLEM SOLVING SITUATIONS - Taurina, Agrita; Engele, Zane (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Introduction. Forming the questions, the ability to listen to different opinions, to evaluate the problem and looking for different ways of solving it, to agree upon a commonly accepted opinion – these all are daily necessities for each person. According to the skills of a child's dialogue speech, these issues can be either more successfully or less effectively solved. During the communication process the teacher and parents can demonstrate to a child an interested, supportive position that ensures the implementation of the values of human pedagogy and develops the socio-linguistic growth of the child's personality. The empirical study examines the techniques of pedagogical work in problem-solving situations of everyday life by using productive questions. Development both of dialogue speech and successful negotiation process are closely related to adult skills that a child often imitates, and environmental conditions.Results, conclusions. Solving negotiations about daily situations, the ability to ask and find the best possible solution during the communication process with a child can ensure a successful acquisition of the Latvian language and the child's ability to implement the dialogue speech more successfully.